Functional Analysis of Adipokinetic Hormone Signaling in Bombyx mori - Hana Sehadova; Yoko Takasu; Anna Zaloudikova; Yu-Hsien Lin; Ivo Sauman; Hideki Sezutsu; Lenka Rouhova; Dalibor Kodrik; Michal Zurovec (Cells, 2020)
Insect adipokinetic hormones (AKHs) are short peptides produced in the corpora cardiaca and are responsible for mobilizing energy stores from the fat body to the hemolymph. Three related peptides, AKH1, AKH2, and AKH/corazonin-related peptide (ACP) as well as three AKH receptors have been reported in Bombyx mori. AKH1 and AKH2 are specific for the AKHR1 receptor, whereas ACP interacts with the other two AKHRs. To assess the effect of the two silkworm AKHs and ACP in the regulation of energy homeostasis we examined the expression pattern of the three peptides and their receptors as well as their effect on the level of carbohydrates and lipids in the hemolymph. Our results support the hypothesis that only AKH1 and AKH2 peptides together with the AKHR1 receptor are involved in the maintenance of energy homeostasis. Because Bombyx AKHR1 (BmAKHR1) seems to be a true AKHR we generated its mutation. The BmAKHR1 mutant larvae display significantly lower carbohydrate and lipid levels in the hemolymph and reduced sensitivity to starvation. Our study clarifies the role of BmAKHR1 in energy homeostasis.